An observational study on the effects of early and late risk factors on the development of childhood obesity in the South of Italy - Raffaele Squeri; Cristina Genovese; Maria Angela Rita Palamara; Giuseppe Trimarchi; Concetta Ceccio; Vittoria Donia; Maria Pecoraro; Giuseppe La Monica; Vincenza La Fauci (Epidemiology, Biostatistics and Public Health)
Background: Child obesity is today one of the greatest health emergencies, on such a large scale as to be considered a global epidemic by the WHO and, unfortunately, Italy holds the worst European record. Methods: We conducted an observational study to investigate the effects of early and late risk factors on the development of primary childhood obesity. We collected anthropometric parameters, information about early risk markers and late risk factors on a sample of 280 children from March 2016 to December 2017. Results: Statistically significant associations emerged between: child's BMI and education level of the mother (p<0.001) and the father (p<0.05); level of parents' education and qualitative variables (subjects’ physical activity level (p<0.05), consumption of carbonated beverages (p<0.05), fruit juices (p <0.05) and snacks (p<0.05); BMI and the presence or absence of a family history of obesity, DM and cardiovascular diseases. Significant linear correlations were found between weight classification (overweight/obese) and the consumption of carbonated drinks (p<0.05), snack consumption (p<0.05), physical activity levels (p<0.001) and duration of sleep in the afternoon (p<0.05). Conclusions: In our sample we found incorrect eating habits to be frequently linked to a low level of parental education; particularly for the mother, the main childcare provider.